NEOGENE HISTORY OF INTRAMONTANE BASINS IN THE WESTERN PART OF THE CARPATHIANS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1990)
Neogene collision of the Carpathians with the European Platform resulted in flysch nappes overthrust in frontal part of the orogene. Tectonic activation of the Paleoalpine-consolidated Centrai Western Carpathians led to modification of their structural pattern. Axis of the main compression rotated from NW-SE to NE-SW. Thrust-reverse faults and ENE-WSW dextral strike- slips were dominant in the Lower Miocene. Movement of the Western Carpathians north-eastward during the Middle and Upper Miocene caused activation of ENE-WSW sinistrai strike-slips and NE-SW normai faults. Pliocene regional extension was manifested mainly by NE-SW normai faults which controlled the sedimentation and form of the basins.
Keywords: Intramontane basins; Neogene; Western Carpathians